The cultural economy of human waste reuse: Perspectives from peri-urban Karnataka, India - Burt, Z.; Prasad, C. S. S.; Drechsel, Pay; Ray, I. (IWA Publishing, 2021)
Safely managed waste reuse may be a sustainable way to protect human health and livelihoods in agrarian-based countries without adequate sewerage. The safe recovery and reuse of fecal sludge-derived fertilizer (FSF) has become an important policy discussion in low-income economies as a way to manage urban sanitation to benefit peri-urban agriculture. But what drives the user acceptance of composted fecal sludge? We develop a preference-ranking model to understand the attributes of FSF that contribute to its acceptance in Karnataka, India. We use this traditionally economic modeling method to uncover cultural practices and power disparities underlying the waste economy. We model farmowners and farmworkers separately, as the choice to use FSF as an employer versus as an employee is fundamentally different. We find that farmers who are willing to use FSF prefer to conceal its origins from their workers and from their own caste group. This is particularly the case for caste-adhering, vegetarian farmowners. We find that workers are open to using FSF if its attributes resemble cow manure, which they are comfortable handling. The waste economy in rural India remains shaped by caste hierarchies and practices, but these remain unacknowledged in policies promoting sustainable ‘business’ models for safe reuse. Current efforts under consideration toward formalizing the reuse sector should explicitly acknowledge caste practices in the waste economy, or they may perpetuate the size and scope of the caste-based informal sector.